2010
DOI: 10.1161/circulationaha.109.850677
|View full text |Cite
|
Sign up to set email alerts
|

Passive Stiffness of Myocardium From Congenital Heart Disease and Implications for Diastole

Abstract: An elevated end-diastolic pressure in pressure-overloaded, but not volume-overloaded, ventricles was related to increased myocardial stiffness. The greater stiffness of pressure-overloaded compared with volume-overloaded myocardium was due to the higher stiffness of both the extracellular matrix and myocytes. The transition from normal to very-low stiffness myocytes may mark irreversible dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 39 publications
8
86
0
4
Order By: Relevance
“…However, distinct results have been found in aortic stenosis patients, with either a switch to N2B (Williams et al 2009) or a switch to N2BA (Borbély et al 2009b) compared to a donor (non-failing hearts) group. In another variant of heart disease, hypertrophic cardiomyopathy (Chaturvedi et al 2010), the cardiac titin isoform did not change compared to donor groups. Thus, the co-expression of titin isoforms provides a structural basis for myofibrillar elastic diversity in different vertebrate species and is one of the mechanisms that regulate myocardial passive stiffness.…”
Section: Sarcomeric Proteins: Elastic Filamentsmentioning
confidence: 84%
“…However, distinct results have been found in aortic stenosis patients, with either a switch to N2B (Williams et al 2009) or a switch to N2BA (Borbély et al 2009b) compared to a donor (non-failing hearts) group. In another variant of heart disease, hypertrophic cardiomyopathy (Chaturvedi et al 2010), the cardiac titin isoform did not change compared to donor groups. Thus, the co-expression of titin isoforms provides a structural basis for myofibrillar elastic diversity in different vertebrate species and is one of the mechanisms that regulate myocardial passive stiffness.…”
Section: Sarcomeric Proteins: Elastic Filamentsmentioning
confidence: 84%
“…In pressure-overloaded heart disease, the ventricle is stiffer than normal, resulting in diastolic heart failure. It was shown that muscle strips from these hearts are significantly stiffer than either normal or volume-overloaded muscle (Chaturvedi et al, 2010). The increased stiffness could be attributed to muscle hypertrophy, which is characterized by an increased number of elastic units arranged in a parallel manner.…”
Section: Cardiovascular Diseasementioning
confidence: 98%
“…Fibrosis may cause slippage of cardiomyocytes, resulting in ventricular wall thinning and consequent ventricular dilation [15]. Additionally, enhanced ECM synthesis and reduced degradation lead to enlarged mechanical stiffness and cardiac dysfunction [16]. Furthermore, increased deposition of ECM among cardiomyocyte layers may interrupt their electrical coupling, resulting in weakened cardiac contraction and an increased risk of arrhythmia [17].…”
Section: Introductionmentioning
confidence: 99%